Low dose of hydroxyethyl starch impairs clot formation as assessed by viscoelastic devices. (June 2014) - Tynngård, Nahreen; Berlin, Gösta; Samuelsson, Anders; Berg, Sören
Abstract Objective. High doses of the synthetic colloid hydroxyethyl starch (HES) used for plasma expansion have been associated with impaired haemostasis and hypocoagulation. Less is known about effects on clot formation in the low haemodilutional range (< 40%). This study evaluated the effects of low haemodilution with HES and albumin on coagulation using two different viscoelastic methods. Methods. Clot formation was studied in vitro in healthy donor blood after 10% and 30% haemodilution with 60 g/L HES 130/0.4 or 50 g/L albumin with free oscillation rheometry (FOR) and rotational thromboelastography. Results. Clotting time was not significantly affected at 10% haemodilution but was prolonged with both substances at 30% dilution (p < 0.01–0.001). The effect was significantly more pronounced with HES than with albumin. The elasticity of the clot was slightly reduced at 10% dilution with albumin, more pronounced at 10% dilution with HES (p < 0.05), further reduced at 30% dilution with albumin and to a still greater extent at 30% dilution with HES (p < 0.05). With albumin the functional activity of fibrinogen was not reduced in excess of the dilutional effect. HES in contrast produced a further reduction in clot elasticity than caused by mere dilution at both 10% and 30% dilutions (p < 0.001). Conclusions. There is an adverse effect on clot formation even at low grade haemodilution with both albumin and HES. The effect on coagulation is significantly more pronounced with HES than with albumin.